1994
DOI: 10.1016/0026-0495(94)90041-8
|View full text |Cite
|
Sign up to set email alerts
|

Variations in high-density lipoprotein subclasses during the menstrual cycle

Abstract: In a study of 41 healthy premenopausal women, plasma high-density lipoprotein-2a (HDL 2a ) levels (ie, HDL of diameter 8.8 to 9.7 nm) were significantly higher during the luteal phase than during the follicular phase of the cycle. There was no significant variation in HDL 2b or any of the HDL 3 subclasses.Plasma high-density lipoprotein (HDL) cholesterol and apolipoprotein (apo) A-I are reported to be higher during the luteal phase than during the follicular phase of the menstrual cycle [1][2][3]. This may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Fortunately, in the research venue, a measure of the subclass concentration that is proportional to the true concentration is generally adequate. Because most statistical tests are location-and scale-invariant (regression analyses, correlations, t tests, analysis of variance, analysis of covariance, and, of course, nonparametric tests), the correct significance levels and correlation coefficients can be obtained, even if the true concentrations of the individual HDL subclasses are unknown, provided a measure of concentration is used that differs from the true concentration through the addition or multiplication of constants [37,[68][69][70][71][72]. A corollary is that the absorbance itself may be used to assess the relationships of the subclass concentrations to other variables and to test for group differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, in the research venue, a measure of the subclass concentration that is proportional to the true concentration is generally adequate. Because most statistical tests are location-and scale-invariant (regression analyses, correlations, t tests, analysis of variance, analysis of covariance, and, of course, nonparametric tests), the correct significance levels and correlation coefficients can be obtained, even if the true concentrations of the individual HDL subclasses are unknown, provided a measure of concentration is used that differs from the true concentration through the addition or multiplication of constants [37,[68][69][70][71][72]. A corollary is that the absorbance itself may be used to assess the relationships of the subclass concentrations to other variables and to test for group differences.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma HDL 2a levels are reported to be lower 14 days, and higher 22 to 32 days, after the beginning of the last menstrual period [71]. Postmenopausal estrogen replacement appears to be associated with increases in HDL 3a and HDL 2a [75].…”
Section: Effects Of Gender and Agementioning
confidence: 97%
“…Studies of Indians overseas have included examination of risk factors in immigrant Indians living in such diverse countries as Singapore (Hughes et al, 1998), Britain (Balarajan, 1991), South Africa (Cosnett, 1957) and USA (Anand et al, 1998). Some reports indicate that this excess of risk may not apply uniformly to people from all areas of the subcontinent, for example, the Punjab (Balarajan et al, 1984), however, even people from this region have been shown to have an excess of nonbiochemical risk factors for CHD (Williams et al, 1994). Recent studies of cardiac patients of British and Indian origin (2), and of sons of cardiac patients of Indian and North European origin (Shaukat et al, 1995) confirm these findings, and further attest to the elevation of Lp(a) in South Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Five HDL subclasses have so far been identified by this method: HDL 3c (7.2 to 7.8 nm in diameter), HDL 3b (7.8 to 8.2 nm), HDL 3a (8.2 to 8.8 nm), HDL 2a (8.8 to 9.7 nm), and HDL 2b (9.7 to 12 nm) [1]. Prior studies show that different HDL subclasses exhibit specific relationships to exercise [2], weight loss [2], age [3], menstrual status [4], adiposity [3], alcohol intake [3], post-menopausal estrogen replacement [3], other lipoproteins [5,6], and shared genetic and environmental influences within families [7]. Case-control and angiographic studies suggest that coronary heart disease risk may be increased when HDL 2b is decreased relative to HDL 3c and HDL 3b [8][9][10].…”
Section: Introductionmentioning
confidence: 99%